1985
DOI: 10.1159/000180056
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Control of Growth and Prolactin Autoregulation in Cultured Human Pituitary Cells

Abstract: A human pituitary cell line (18-54, SF) grows in serum-free medium and secretes prolactin (PRL). Autoregulation of pituitary cell growth and PRL production by exogenously supplied ovine PRL (oPRL) was investigated. Human PRL (hPRL) and oPRL stimulated pituitary cell growth up to 92% and 85%, respectively, at hPRL and oPRL additions of 100-1,000 ng/ml. Short-term (1 h) incubation of the cells with oPRL decreased hPRL secretion from the cells by 72% at 10 ng/ml addition. Intracellular hPRL was stimulated under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
(7 reference statements)
2
4
0
Order By: Relevance
“…The inhibitory growth response of lactotrophs to PRL is quite different from the proliferative effect exhibited in nonpituitary cell types (14)(15)(16)(17)(18)(19)(21)(22)(23)(24)(25), in human prolactinoma cells (44), and in a transformed rat lactotroph cell line (20). It is, however, consistent with models of PRL effects on EGF and TGF-α signaling cascades.…”
Section: Discussionsupporting
confidence: 62%
“…The inhibitory growth response of lactotrophs to PRL is quite different from the proliferative effect exhibited in nonpituitary cell types (14)(15)(16)(17)(18)(19)(21)(22)(23)(24)(25), in human prolactinoma cells (44), and in a transformed rat lactotroph cell line (20). It is, however, consistent with models of PRL effects on EGF and TGF-α signaling cascades.…”
Section: Discussionsupporting
confidence: 62%
“…The inhibitory growth response of lactotrophs to PRL is quite different from the proliferative effect exhibited in nonpituitary cell types (14)(15)(16)(17)(18)(19)(21)(22)(23)(24)(25), in human prolactinoma cells (44), and in a transformed rat lactotroph cell line (20). It is, however, consistent with models of PRL effects on EGF and TGF-α signaling cascades.…”
supporting
confidence: 62%
“…PRL acts as a proliferative factor in some tissues, such as mammary gland, prostate, and lymphoid cells (11), but exerts proapoptotic actions in others, such as luteal cells (12) and hair follicles (10). Although older studies using in vitro cell cultures suggested that PRL could act as a growth factor for anterior pituitary cells (15,17), more recent investigations involving genetically modified mouse models actually achieved opposite conclusions because lack of PRL activity in PRL-knockout mice (PRL Ϫ/Ϫ ) and PRLR knockout-mice (PRLR Ϫ/Ϫ ) was shown to lead to pituitary hyperplasia and tumor development (8,27). Also, it has been shown that exogenous PRL decreases in vitro lactotrope proliferation in D2R-knockout mice (D2R Ϫ/Ϫ ) (27), suggesting that PRL may regulate the size of the population of anterior pituitary cells, particularly lactotropes.…”
mentioning
confidence: 99%